2018
DOI: 10.3390/inorganics6020054
|View full text |Cite
|
Sign up to set email alerts
|

S–H Bond Activation in Hydrogen Sulfide by NHC-Stabilized Silyliumylidene Ions

Abstract: Reactivity studies of silyliumylidenes remain scarce with only a handful of publications to date. Herein we report the activation of S-H bonds in hydrogen sulfide by mTer-silyliumylidene ion A (mTer = 2,6-Mes 2 -C 6 H 3 , Mes = 2,4,6-Me 3 -C 6 H 2 ) to yield an NHC-stabilized thiosilaaldehyde B. The results of NBO and QTAIM analyses suggest a zwitterionic formulation of the product B as the most appropriate. Detailed mechanistic investigations are performed at the M06-L/6-311+G(d,p)(SMD: acetonitrile/benzene)/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“…The imidazolium salt could then be separated by repeated washing with hexane, in which the light salt forms a fine suspension while the heavy silyliumylidene salt settles, to give yields of 45–54 %. This yield was later improved to 66 % as dilution enables the separation of the rapidly‐precipitated imidazolium salt prior to crystallisation of the silyliumylidenes salt …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The imidazolium salt could then be separated by repeated washing with hexane, in which the light salt forms a fine suspension while the heavy silyliumylidene salt settles, to give yields of 45–54 %. This yield was later improved to 66 % as dilution enables the separation of the rapidly‐precipitated imidazolium salt prior to crystallisation of the silyliumylidenes salt …”
Section: Discussionmentioning
confidence: 99%
“…This yield was later improved to 66 % as dilution enables the separation of the rapidly-precipitated imidazolium salt prior to crystallisation of the silyliumylidenes salt. [34] It is worth noting that Sasamori, Tokitoh and Matsuo have prepared arylsilyliumylidene ions by addition of NHC to an appropriate disilene precursor Ar(Br)Si=Si(Br)Ar, [20] and recently reported that our route is also effective for this, although the separation of by-product is more difficult in their case. [23] The X-ray diffraction (XRD)-determined structure of 1 a gave a sum of bond angles from the silicon centre and the three carbon atoms bound to it of 310.28, which shows substantial pyramidalisation.…”
Section: Synthesis and Structurementioning
confidence: 94%
See 1 more Smart Citation
“…[13] Exploration of the reactivity of silyliumylidene (1)t owards chalcogens and H 2 Se nabled an access to NHC-stabilized heavierc halcogen silaacylium derivatives [14] and thiosilaaldehyde. [15] Herein, we report our study devotedt ot he synthesis of as ilaaldehyde, isolated as a Si,O-donor-acceptor complex, and its unique reactivity showing strong relationship to the chemistry of carbonyl congeners ( Figure 1b).…”
mentioning
confidence: 99%
“…They also discuss the isolation of arylsilyliumylidene ions through the dehydrobromination with four NHC equivalents. In the course of the reactivity study on the NHC-coordinated silyliumylidene ion, Porzelt et al describe the activation of the S-H bond in hydrogen sulfide by the arylsilyliumylidene ion, resulting in the formation of an NHC-coordinated thiosilaaldehyde [8]. DFT (density functional theory) calculations have been employed to examine the zwitterionic character of NHC-coordinated thiosilaaldehyde, and the reaction mechanism for the formation has also been computationally investigated.…”
mentioning
confidence: 99%